Two Multicenter Surveys on Equine Back-Pain 10 Years a Part - Riccio, Barbara; Fraschetto, Claudia; Villanueva, Justine; Cantatore, Federica; Bertuglia, Andrea (Frontiers in Veterinary Science, 2018)
Despite back-pain being a common cause of poor performance in sport horses, a tailored diagnostic workflow and a consolidated therapeutic approach are currently lacking in equine medicine. The aim of the study was to assess the evolution in the veterinarian approach to diagnose and treat back-pain over a 10 years period. To investigate this topic, two surveys were addressed to equine veterinarians working in practice throughout Europe ten years apart (2006 & 2016). The answers were organized in an Excel dataset and analysed. There were 47 respondents in 2006 and 168 in 2016, from 8 European Countries. The main reasons for examining horses with back-pain were poor performance (76%), behavioural issues (68%) and lameness (50%). When assessing back pain, 97% of respondents applied careful digital pressure over paravertebral muscles, 90% of them used digital back mobilization and 69% was detecting areas of localised heat. The use of diagnostic analgesia to confirm the source of pain was rarely employed. Radiography and ultrasonography were the most frequent diagnostic imaging modalities used to investigate the causes of back-pain in both surveys. Obtaining a definitive diagnosis in horses with back-pain is considered challenging due to the reduced accessibility of the area and the variability in the pain manifestations. Corticosteroids injections were used for local treatments by 80% of respondents in 2006 and 92% in 2016. Recently, ultrasonography has been extensively used during the injections of the vertebral articular facets and sacroiliac joints region. The use of complementary therapies was restricted to a low percentage of respondents in the first survey (20%) but it increased over the decade. In 2016, a wider percentage of respondents considered osteopathy (40%), kinesiotherapy (29%) and acupuncture (22%) when treating back disorders compared to 2006. The structural differences of the two surveys did not enable a direct data comparison. Based on the results of this surveys, however, veterinarians should be sensitized to the back-pain problems and seek to integrate findings from clinical research studies in their daily practice.